A reformative framework for processes from building permit issuing to property ownership in Turkey. (February 2021) - Guler, Dogus; Yomralioglu, Tahsin
Highlights: The efforts w.r.t. building permit processes, land administration, and 3D city modeling in Turkey are elaborately examined. A framework including building permit procedures, 3D registration of condominium, and update of 3D city models is proposed. The use of digital building models is suggested within the context of the proposed framework. The digitalization and interoperability underpin the reformative framework. Abstract: A smart built environment has become necessary for ensuring social well-being due to uncontrolled population growth and unrestrainable urban sprawl. In this connection, effective land administration is a significant element to actualize sustainable development. Yet existing building permit procedures fail to satisfy the need for current construction demands because of the insufficient transparency and inefficient procedures. Two dimensional (2D) based systems also remain incapable to unambiguously delineate the property ownership related to complex buildings. Keeping up-to-date the three dimensional (3D) urban models is another key for smart cities but this issue has become difficult owing to the rapid changes in the cities. In this sense, this paper first examines thoroughly the current situation in Turkey in terms of the building permit procedures, land administration, and 3D city modeling. Then, the paper detailedly proposes a reformative framework. The framework consists of the use of digital building models for both building permit processes and 3D registration of property ownership, as well as updating the 3D city model databases. The proposed framework is evaluated in terms of its applicability with a discussion of the prospective directions.